Bipolar transurethral resection of large prostate >100 gm: single center experience - Mamdoh, Hussein; Elbendary, Mohamed; Habib, Enmar; Hassan, Ayman (International Surgery Journal, 2021)
Background: Benign prostatic hyperplasia (BPH) is a common urological finding in aged men. It may be associated with deterioration of the patient’s quality of life as it may cause lower urinary tract symptoms (LUTS), urinary retention, and deterioration of the renal function. The gold standard treatment option is transurethral resection of prostate (TURP) in patients with prostate up to 80g in size. However, in larger prostates (>80 g), laser or bipolar enucleation of the prostate is considered the treatment of choice. In this setting, we decided to report a single center experience with bipolar TURP for large prostates (>100 g). Methods: The database of our center was retrospectively reviewed to identify all the patients undergoing bipolar TURP for large prostates (>100 g) between January 2018 and January 2019. The following data was collected, age, prostate size in grams, urinalysis and culture. Moreover, the operative time, resected tissue weight, complications, hospitalization, and catheterization times were also collected Furthermore, urinary tract ultrasound (including the assessment of post voiding residual urine [PVR]), uroflowmetry (including the peak urinary flow [Qmax]), and IPSS were assessed preoperatively, at one, and 12 months postoperatively. Results: Eight were retrieved from the database and were included in the current study. The median prostate size was 115 grams. All cases were completed by B-TURP without the need for conversion to open prostatectomy and the operative time ranged from 65 to 90 minutes. All the patients showed significant improvement of the IPSS, Qmax, and PVR at one and 12 months follow up. Only three patients in the current series (37.5%) suffered from complications. Conclusions: B-TURP can be used safely for the management of large prostates (>100 g); however, further studies are required to confirm these results.